Evaluasi Keamanan Karet Silikon pada Dental Holder Inovatif: Sebuah Studi Intervensi pada Radiografi Periapikal - Jannah, Marichatul; Erfansyah, Muhammad; Tsania, Novia Putri; Nurrachman, Aga Satria; Ramadhani, Nastiti Faradilla (Poltekkes Kemenkes Semarang, 2026)
Background: Silicone base dental holders have been introduced in periapical radiography to improve ergonomic and patient comfort. However, repeated intraoral use raises safety concerns related to microbial contamination due to direct contact with saliva and the potential for biofilm formation. This study aimed to evaluate the sterility of silicone based dental holders following clinical use, routine antiseptic washing, and seven days of storage. Methods: This experimental laboratory study employed a post-test with control group design. Thirty silicone dental holder samples were divided into an intervention group (used clinically; n = 15), and control group (unused; n= 15). After clinical use, intervention samples was washed using antiseptic soap according to standard hospital procedures and stored in sterile containers at room temperature for seven days. Sterility testing was performed using Heart Infusion Broth (HIB) culture medium incubated at 37°C for five days. Bacterial growth was assessed based on medium turbidity. Results: All samples (100%) in both groups showed turbidity in the HIB medium, indicating bacterial contamination despite prior antiseptic washing. The findings demonstrate that manual cleansing with antiseptic soap alone is insufficient to eliminate microbial colonization on silicone dental holders. Conclusions: Routine antiseptic washing and short term storage were insufficient to ensure the sterility of silicone dental holders. These finding highlight the need for more effective sterilization protocols to support safe reuse in periapical radiographic practice.